Ten years of digital visual restoration systems - KOKARAM, ANIL CHRISTOPHER (My University, 2007)
With the growth in marketability of all forms of visual media comes the need to exploit archive material more effectively, and a requirement to guarantee picture quality regardless of the originating medium. Some kind of touch-up or restoration is rapidly becoming a ?must have? in the visual production cycle. This paper reviews the development and impact of Digital Restoration Systems in the broadcast television and film industry over the last ten years. It presents some unifying ideas as well as the relevance and challenges of defect treatment in such harsh picture environments.
Image Processing
IEEE International Conference on Image Processing, 2007. ICIP 2007.
PUBLISHED
Keywords: Video Restoration; Post-Production; Motion Estimation; Bayesian Inference; Example Based Image Processing; Inpainting; Object removal